2009
DOI: 10.1016/j.ijgo.2009.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water intake on the waiting time prior to gynecologic transabdominal ultrasound

Abstract: Objective: To investigate the effect of volume of water intake on the length of time before the bladder is sufficiently full prior to undergoing transabdominal ultrasound. Methods: Ninety-three patients scheduled for transabdominal ultrasound were enrolled between November 2007 and April 2008 and randomly allocated to 3 study groups by volume of water intake: 300, 400, and 500 mL. The total waiting time was recorded when the bladder was sufficiently full to undergo transabdominal ultrasound. The final bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Another possibility is the volume of water ingested was not sufficient enough to reduce waiting time. 13 The previous study is in accordance with our study. We used the same volume of water (range 300-500 ml) and did not find significant differences in waiting time.…”
Section: Discussionsupporting
confidence: 89%
“…Another possibility is the volume of water ingested was not sufficient enough to reduce waiting time. 13 The previous study is in accordance with our study. We used the same volume of water (range 300-500 ml) and did not find significant differences in waiting time.…”
Section: Discussionsupporting
confidence: 89%
“…The intake of the 200 ml of standardized liquid meal was scheduled at 60 min after water intake because it has been previously demonstrated that a mean time of 68.65 ± 30.12 and 54.38 ± 12.75 min are necessary to 500 and 300 ml of water to fill the bladder, respectively [19]. For this reason, for 200 ml of water, 1 h is an appropriate period of time to go through the PBF and to be eliminated by renal excretion.…”
Section: Discussionmentioning
confidence: 99%